High-performance supercapacitors of carboxylate-modified hollow carbon nanospheres coated on flexible carbon fibre paper: Effects of oxygen-containing group contents, electrolytes and operating temperature - Phattharasupakun, N; Wutthiprom, J; Suktha, P; Iamprasertkun, P; Chanlek, N; Shepherd, C; Hadzifejzovic, E; Moloney, M; Foord, J; Sawangphruk, M (Elsevier, 2017)
Although carbon black nanoparticles (CBs) at ca. 10 wt.% are widely used as a conductive additives for energy storage electrodes for lithium ion batteries and supercapacitors, they are not extensively used as the active materials for such devices due to their poor ionic conductivity and wettability. In this work, CBs were oxidized by a process of refluxing with conc. HNO3 for 6-72 h, providing oxidized CBs (OCBs) with different oxygen-containing groups (i.e., carboxyl, hydroxyl, and carbonyl) and contents. The OCBs refluxed for 12 h have ca. 2.0-fold higher accessible active surface area than that of the pristine CBs. The as-fabricated symmetric supercapacitor using OCBs refluxed for 12 h with a [BMP][DCA] ionic liquid electrolyte exhibits specific energy and maximum specific power of 88 Wh kg-1 and 8429 W kg-1, respectively with the capacitance retention over 97% after 6000 cycles. A single coin-cell supercapacitor prototype fully charged can supply electrical power to a red LED over 24 min. This device may be practically used as a battery replacement in high power applications.